2015
DOI: 10.1007/s11596-015-1382-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL33/ST2 signal pathway gene polymorphisms with myocardial infarction in a Chinese Han population

Abstract: This study investigated the relationship between IL-33/ST2 signal pathway gene polymorphisms and myocardial infarction (MI) in Han Chinese. A case-control association analysis was performed on a total of 490 MI patients (MI group) and 929 normal subjects (NC group). Sequenom Mass Array and Taqman genotyping technique were used to analyze the tag single nucleotide polymorphisms (SNPs) in the genes encoding IL-33, ST2, and IL-1RaP (rs11792633, rs1041973 and rs4624606). The results showed that the frequencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…When assessing 1146 CAD patients and age-and sex-matched controls, no significant association between gene polymorphisms in the IL-33 or ST2 genes and presence/absence of CAD was demonstrated [28]. Similar results were found when comparing patients with previous MI vs. control subjects [29]. Notably, the relevance of these analyses is limited by the small number of gene variants explored, and by the lack of genotype-phenotype correlations, making it difficult to clarify the relationship with ST2/IL-33 signalling.…”
Section: Human Studiessupporting
confidence: 66%
“…When assessing 1146 CAD patients and age-and sex-matched controls, no significant association between gene polymorphisms in the IL-33 or ST2 genes and presence/absence of CAD was demonstrated [28]. Similar results were found when comparing patients with previous MI vs. control subjects [29]. Notably, the relevance of these analyses is limited by the small number of gene variants explored, and by the lack of genotype-phenotype correlations, making it difficult to clarify the relationship with ST2/IL-33 signalling.…”
Section: Human Studiessupporting
confidence: 66%
“…Soluble IL-1RAcP interacts with the sST2-IL-33 complex to impair IL-33 signaling [23]. Previous studies indicated the importance of IL-1RAcP in cardiovascular diseases, such as myocardial infarction and EH [24,25]. Nikpay and coworkers found that the IL-1RAcP polymorphism rs4687150 is associated with the risk of EH 25 .…”
Section: Association Analyses For Strati Ed Traditional Risk Factorsmentioning
confidence: 99%
“…Studies that did not meet these standards were excluded. Thus, seven casecontrol studies met our inclusion criteria for qualitative data analysis, and contained a total of 10686 cases and 10775 healthy subjects (7,8,(37)(38)(39)(40)(41). Two researchers simultaneously screened the studies back-to-back and obtained consistent results.…”
Section: Study Characteristicsmentioning
confidence: 99%